Role of the Ketogenic Diet in Psychiatry: Review of Clinical Trials and Case Studies - Minkiewicz, Magda; Musialska, Dominika; Bolek, Michał; Fidyk, Monika; Jagieła, Bartosz; Kędzia, Aleksandra (Quality in Sport, 2025)
The ketogenic diet (KD) has gained a lot of recognition as a treatment in refractory epilepsy. Due to its success, more and more researchers have begun to question whether this diet would have a similar positive influence on patients suffering from various psychiatric disorders. This paper explores the use of the ketogenic diet in psychiatric conditions, particularly in mood disorders, schizophrenia, and neurodegenerative diseases. The initial studies have a rather promising outcome, but more evidence needs to be gathered in order to ensure this diet is a safe and credible tool in managing psychiatric symptoms. This review discusses current studies, challenges, and future research directions.